2022
DOI: 10.1186/s12931-022-02033-6
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity burden and survival in patients with idiopathic pulmonary fibrosis: the EMPIRE registry study

Abstract: Background Patients with idiopathic pulmonary fibrosis (IPF) frequently have multiple comorbidities, which may influence survival but go under-recognised in clinical practice. We therefore report comorbidity, antifibrotic treatment use and survival of patients with IPF observed in the multi-national EMPIRE registry. Methods For this prospective IPF cohort, demographics, comorbidities, survival and causes of death were analysed. Comorbidities were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 49 publications
2
4
0
Order By: Relevance
“…The burden of comorbidity in patients with IPF has not been studied as extensively as it has in COPD patients. Estimates of comorbidity prevalence vary widely between studies, but the rates of multiple prevalent comorbidity identified in our study are in line with those documented in prior registry studies [ 9 , 27 ]. Regarding individual comorbidities, previous studies have generated comparable estimates of the prevalence of hypertension [ 9 , 28 ], cardiac disease [ 9 , 27 ], thyroid disease [ 27 ], GERD [ 9 ], cerebrovascular disease [ 10 ], heart failure [ 10 ] in IPF populations (Table 1 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The burden of comorbidity in patients with IPF has not been studied as extensively as it has in COPD patients. Estimates of comorbidity prevalence vary widely between studies, but the rates of multiple prevalent comorbidity identified in our study are in line with those documented in prior registry studies [ 9 , 27 ]. Regarding individual comorbidities, previous studies have generated comparable estimates of the prevalence of hypertension [ 9 , 28 ], cardiac disease [ 9 , 27 ], thyroid disease [ 27 ], GERD [ 9 ], cerebrovascular disease [ 10 ], heart failure [ 10 ] in IPF populations (Table 1 ).…”
Section: Discussionsupporting
confidence: 90%
“…Estimates of comorbidity prevalence vary widely between studies, but the rates of multiple prevalent comorbidity identified in our study are in line with those documented in prior registry studies [ 9 , 27 ]. Regarding individual comorbidities, previous studies have generated comparable estimates of the prevalence of hypertension [ 9 , 28 ], cardiac disease [ 9 , 27 ], thyroid disease [ 27 ], GERD [ 9 ], cerebrovascular disease [ 10 ], heart failure [ 10 ] in IPF populations (Table 1 ). The prevalence of diabetes was lower in our IPF cohort than prior studies (11% versus 23–45%) [ 9 , 10 , 29 ], but depression was more commonly seen in our study than in prior reports (23% versus 3–15%) [ 9 , 10 , 29 ].…”
Section: Discussionsupporting
confidence: 90%
“…The EMPIRE registry study included 3,580 IPF patients from multiple countries, and at the time of enrollment, 91.3% of patients had been diagnosed with at least one comorbidity, with over one-third (37.8%) reporting four or more comorbidities. The 5-year survival rates for patients without common complications and with 1, 2, 3, and ≥ 4 complications were 53.7%, 48.4%, 47.0%, 43.8%, and 41.1%, respectively [120].…”
Section: Fat Deposition Promotes Complications In Ipf Intensifies The...mentioning
confidence: 93%
“…Our study addresses a gap in knowledge by identifying comorbidities associated with poor prognosis specifically in hospitalized patients with AE-IPF. The burden of comorbidities is noted to be high among IPF patients, and increasing number of comorbidities has been associated with worse survival [37]. However, to our knowledge, our study is unique in examining the impact of comorbidity on mortality in AE-IPF.…”
Section: Strengths and Limitationsmentioning
confidence: 95%